Rational Choice Theory as a Philosophical Basis for Voluntary Disclosure of Anti-Fraud Policy - Kurniawati, Anggreni Dian; Syamsuddin, Muhammad Mukhtasar (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
The disclosure of anti-fraud policies by non-financial companies in Indonesia is still voluntary, unlike that of financial and banking companies that which are required to make such disclosures. In the context of voluntary disclosure of anti-fraud policies, rational choice theory assumes that companies will make disclosure if the benefits are perceived to outweigh the risks. However, in reality, non-economic motives additionally take a role in decisions pertaining to this disclosure, in addition to rational ones. This research criticizes the rational choice theory by exploring whether voluntary disclosure decisions by non-financial companies are genuinely rational or influenced by significant non-economic factors such as moral, cultural, and corporate image. This research provides a new perspective for non-financial companies in Indonesia to consider non-economic factors in decision-making regarding the disclosure of anti-fraud policies and to develop views in the philosophy of economics on the importance of social and moral factors in economic decision-making about transparency and accountability. This study concerns the economic rationality assumption in the voluntary disclosure of anti-fraud measures by non-financial enterprises in Indonesia, emphasizing the importance of social and organizational culture elements. The findings indicate that a purely rational approach may not always be effective, underlining the importance of integrating ethical ideals and economic philosophy to promote transparency motivated by moral principles rather than financial gain.